The representation of children in the sculptures of the Santo Antônio cemetery/ES: an iconographic and memorial analysis - Rodrigues, Isis Santana; Cirillo, Aparecido José (Revista do Colóquio, 2024)
This research is the result of a survey and analysis of the Santo Antônio cemetery, ES, based on the representation of children in cemetery art. The analysis consisted of a study of photographic and sculptural elements, highlighting the role of cemetery art in the culture of Espírito Santo, and its correlation with different peoples and traditions around the world, making us reflect on the values ​​and traditions of a given society.